AGAMA ALAT POLITIK - Muhammad Jamil (Fakultas Agama Islam Universitas Tjut Nyak Dhien, 2018)
This article is aimed at critizing the political reasoning of the Ahl as-Sunnah wa al-Jamâ’ah. The discussion will be focused firstly on the text (hadîth) criticism which has been proved as weak and “corrupted” by the Ash’arites by interpreting the Ahl as-Sunnah wrongly as the only sect that will be saved. Secondly, ijmâ’ (consensus of the great companions of the Prophet) as a basis of their political reasoning by regarding historical experiences of moslems of the first generation as normative examples for the successors justified, directly or indirectly, “the logic of power” in their political theory. Finally, the plea of “moderation” which is indeed, an on-going proccess and has been developed inconsistently, not only made moral passivity, but justified undoubtedly upon it political opportunism.